2020
DOI: 10.3390/ijms21249401
|View full text |Cite
|
Sign up to set email alerts
|

Differential Contribution of N- and C-Terminal Regions of HIF1α and HIF2α to Their Target Gene Selectivity

Abstract: Cellular response to hypoxia is controlled by the hypoxia-inducible transcription factors HIF1α and HIF2α. Some genes are preferentially induced by HIF1α or HIF2α, as has been explored in some cell models and for particular sets of genes. Here we have extended this analysis to other HIF-dependent genes using in vitro WT8 renal carcinoma cells and in vivo conditional Vhl-deficient mice models. Moreover, we generated chimeric HIF1/2 transcription factors to study the contribution of the HIF1α and HIF2α DNA bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…We also investigated the expression of SLC7A5 and the chaperone SLC3A2 which work in tandem with SLC1A5 to export glutamine and drive leucine uptake necessary for proliferation and mTORC1 regulation although this mechanism seems to be cell type-dependent ( 61 ). SLC7A5 has also been shown to be regulated through HIF-2α ( 46 , 62 ). Our results showed decrease of the three SLC at the mRNA level in response to STF in VHL- cells while their levels are either unchanged or stimulated in VHL+.…”
Section: Discussionmentioning
confidence: 99%
“…We also investigated the expression of SLC7A5 and the chaperone SLC3A2 which work in tandem with SLC1A5 to export glutamine and drive leucine uptake necessary for proliferation and mTORC1 regulation although this mechanism seems to be cell type-dependent ( 61 ). SLC7A5 has also been shown to be regulated through HIF-2α ( 46 , 62 ). Our results showed decrease of the three SLC at the mRNA level in response to STF in VHL- cells while their levels are either unchanged or stimulated in VHL+.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a similar conserved consensus DNA binding site, HIF-1 and HIF-2 bind different but overlapping sets of sites in chromatin and transactivate only partially overlapping patterns of gene expression. It has been suggested that both the DNA-binding and heterodimerization domain as well as the transactivation domain contribute to HIFα isoform selectivity and accordingly target gene selectivity [39]. Correspondingly, Ortmann and coworkers have recently demonstrated HIF-selective recruitment through its PAS-B domain of the histone 3 lysine 4 (H3K4) methyltransferase SET1B, resulting in site-specific H3K4 methylation and rapid activation of HIF target genes [40].…”
Section: Discussionmentioning
confidence: 99%
“…Inactivation of the VHL tumor suppressor gene is the signature initiating event in clear cell renal cell carcinoma (ccRCC), which is the most common form of kidney cancer [ 66 ]. VHL mutation leads to abnormal constitutive stabilization of HIF-1α and HIF-2α proteins in normal oxygen conditions.…”
Section: Hif-2α In Different Cell Typesmentioning
confidence: 99%